Phylogenetic relationship of Sirodotia species (Batrachospermales, Rhodophyta) in North and South America - Necchi Jr., Orlando [UNESP]; Vis, Morgan L.; Oliveira, Mariana C. (My University, 2007)
Sequence data from the RUBISCO large subunit (rbcL) plastid gene and nuclear small-subunit ribosomal DNA (SSU rDNA) were examined for five samples of Sirodotia delicatula from southeastern Brazil. Data from six North American samples, previously identified as S. huillensis and S. suecica were also included in the analysis. Molecular data supported the continued recognition of these three species as separate entities, although one of the North American collections was misidentified. These results were shown to be congruent with morphology, chromosome number and geographic distribution. S. delicatula is more closely related to S. huillensis, both occurring in tropical-subtropical regions, than either to S. suecica with a temperate-boreal distribution. There was little rbcL variation within S. delicatula from Brazil and Costa Rica (the latter a collection previously identified as S. huillensis), with the six samples sequenced diverging from each other by 0-8 bp (0-0.67%). SSU rDNA data set did not provide sufficient resolution to infer phylogenetic relationships among the species of this group due to the low rates of variation (5 bp). Sirodotia was a well-supported clade (100% bootstrap or 1.00 a posteriori probability) based on rbcL sequences. Thus, the results confirm that Sirodotia is a monophyletic group within the Batrachospermales and we continue to recognize it at the generic level. The species S. delicatula, S. huillensis and S. suecica are morphologically and genetically distinct. © 2007 Adac.
Keywords: Batrachospermales; Brazil; Freshwater Rhodophyta; rbcL gene; Sirodotia; SSU rDNA